Living in a Pandemic: Social Isolation and Mental Health - Ostrovsky , Pavlo; Levkiv , Mariana; Boitsaniuk , Svitlana (The Ukrainian Scientific Medical Youth Journal, 2023)
the novel coronavirus disease of 2019 (COVID 2019) has gripped the world with fear, anxiety and confusion, and it is spreading as fast as a virus. In addition to the negative consequences of the infection of COVID-19 for health, the implementation of strict quarantine also affected the world economy. As a result, there is growing concern that the pandemic has harmed the mental health of the general population. Fear, anxiety, and stress are normal responses to perceived or real threats, and when we are faced with uncertainty or something unknown. Thus, it is normal and understandable for people to feel fear in the context of the COVID-19 pandemic. Together with a fear of being infected with a virus during a pandemic like COVID-19, there are significant changes to our daily lifestyle: our movements somewhere is restricted in support of efforts to contain and slow down the spread of the virus. As the COVID-19 pandemic and lockdown measures continue, there is growing interest in the long-term effects on mental health. In this article, we aim to review and summarize the results of various studies that have examined the psycho-sociological consequences of the pandemic and its impact on the mental well-being of population in a general.